Biosynthesis of nitric oxide and its function in organism - Komaszyło, Katarzyna; Zalewska, Renata; Mariak, Zofia; Wiśniewska, Róża (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Nitric oxide (NO) is a gas with diverse biological activities produced from L-arginine by nitric oxide synthetase (NOS). This article provides a short overview of the basic function of NO which takes part in smooth muscle relaxation, neurotransmission, modulation of inflammation in a number of tissues and pathological conditions. The discovery of these new physiological and pathological pathways allows for better understanding of many complex processes. It opens a new field for better treatment of many diseases.